1978
DOI: 10.1111/j.2044-8260.1978.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural correlates of social anxiety

Abstract: High school students' scores on a paper-and-pencil test of social anxiety were correlated with talking, eye contact and gesturing behaviors during a 10-min vidotaped interview. Results showed that high anxious subjects talked less while listening to instruction. They also held the gaze for less total time and in bouts of shorter duration while they were talking;while they were listening, they were significantly more variable in their average bout duration. Within-group variability suggested that non-verbal beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
41
2

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 6 publications
3
41
2
Order By: Relevance
“…There are significant previous findings on the impact of EMS on gaze and head motion [13,6,9]. However, controlling eye motion is beyond the scope of this work.…”
Section: Nonverbal Expression Of Emotional Stabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…There are significant previous findings on the impact of EMS on gaze and head motion [13,6,9]. However, controlling eye motion is beyond the scope of this work.…”
Section: Nonverbal Expression Of Emotional Stabilitymentioning
confidence: 96%
“…Campbell and Rushton observed that people with a high level of anxiety made longer pauses before responding than participants with a normal emotional stability level [6]. Daly cites early work that verifies the presence of speech disturbances in individuals with transient anxiety, in addition to conflicting results on whether individuals with anxiety spend less time talking, or generate fewer utterances [9]. Given the disruption of fluency described by Furnham, we decided to use pauses in speech and gesture as a form of discontinuity for both verbal and nonverbal communication.…”
Section: Nonverbal Expression Of Emotional Stabilitymentioning
confidence: 99%
“…Because socially anxious people expect to embarrass themselves or engage in social blunders, to minimize their apprehension and the likelihood of experiencing rejection, they employ protective rather than acquisitive self-presentation strategies (Arkin, 1987;Arkin, Lake, & Baumgardner, 1986;Meleshko & Alden, 1993;; see Kashdan, McKnight, Richey, & Hofmann, 2009, for a review of the exceptions to these tendencies). For instance, they disengage from social encounters by avoiding eye contact (Daly, 1978;Leary, Knight, & Johnson, 1987) and speaking little (Natale, Entin, & Jaffe, 1979;Pilkonis, 1977). They also agree with others, express neutral attitudes, ask questions, and make acknowledgments (e.g., ''right,'' ''uh-huh'') that encourage others to dominate conversation (Leary et al, 1987;Natale et al, 1979).…”
mentioning
confidence: 99%
“…However, interviews of highschool pupils revealed that high socially anxious pupils had significantly less eye contact with the interviewer than low socially anxious (Daly, 1978). Anxious people also look at the audience less often while having a speech (Eves & Marks, 1991) and their gazing behavior correlates with their actual level of anxiety (Jurich & Jurich, 1974).…”
mentioning
confidence: 99%